Distress Screening Through Patient-Reported Outcomes Measurement Information System (PROMIS) at an Academic Cancer Center and Network Site: Implementation of a Hybrid Model. Issue 11 (November 2021) - Neal, Joel W.; Roy, Mohana; Bugos, Kelly; Sharp, Christopher; Galatin, Peter S.; Falconer, Patricia; Rosenthal, Eben L.; Blayney, Douglas W.; Modaressi, Shiva; Robinson, Ashley; Ramchandran, Kavitha
Abstract : PURPOSE: Cancer care guidelines recommend regular distress screening of patients, with approximately one in three patients with cancer experiencing significant distress. However, the implementation of such programs is variable and inconsistent. We sought to assess the feasibility of implementing a hybrid electronic and paper screening tool for distress in all patients coming to a large academic cancer center and an associated integrated network site. METHODS: Patients at an academic cancer center (Stanford Cancer Center) and its associated integrated network site received either an electronic or on-paper modified Patient-Reported Outcomes Measurement Information System-Global Health questionnaire, to assess overall health and distress. We used the Reach, Effectiveness, Adoption, Implementation, and Maintenance implementation framework to test and report on the feasibility of using this questionnaire. Iterative workflow changes were made to implement the questionnaire throughout the healthcare system, including processes to integrate with existing electronic health records. RESULTS: From June 2015 to December 2017, 53, 954 questionnaires representing 26, 242 patients were collected. Approximately 30% of the questionnaires were completed before the visit on an electronic patient portal. The number of patients meeting the positive screen threshold remained around 40% throughout the study period. Following assessment, there were 3, 763 referrals to cancer supportive services. Of note, those with a positive screen were more likely to have a referral to supportive care (odds ratio, 6.4; 95% CI, 5.8 to 6.9; P < .0001). CONCLUSION: The hybrid electronic and on-paper use of a commonly available patient-reported outcome tool, Patient-Reported Outcomes Measurement Information System-Global Health, as a large-scale distress screening method, is feasible at a large integrated cancer center.